Т. 2; Современные техника и технологии - Малышенко А. М. Александр Максимович; Потылицын А. П. Александр Петрович; Кухта М. С. Мария Сергеевна; Дульзон А. А. Альфред Андреевич; Сидорова О. В. (2015, 2015)
Заглавие с титульного экрана